2003
DOI: 10.1126/science.1088387
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Megawatt Optical Solitons in Hollow-Core Photonic Band-Gap Fibers

Abstract: The measured dispersion of a low-loss, hollow-core photonic band-gap fiber is anomalous throughout most of the transmission band, and its variation with wavelength is large compared with that of a conventional step-index fiber. For an air-filled fiber, femtosecond self-frequency--shifted fundamental solitons with peak powers greater than 2megawatts can be supported. For Xe-filled fibers, nonfrequency-shifted temporal solitons with peak powers greater than 5.5 megawatts can be generated, representing an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
186
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(191 citation statements)
references
References 17 publications
5
186
0
Order By: Relevance
“…For example, in silica core PCFs nonlinearity can be enhanced by the small modal area and group velocity dispersion (GVD) can be controlled by the engineering of the photonic crystal cladding [6,7]. The hollow-core band-gap guiding PCFs can be filled with different gases and used for a variety of nonlinear optical experiments in the low loss and diffraction free geometries with very long interaction distances [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in silica core PCFs nonlinearity can be enhanced by the small modal area and group velocity dispersion (GVD) can be controlled by the engineering of the photonic crystal cladding [6,7]. The hollow-core band-gap guiding PCFs can be filled with different gases and used for a variety of nonlinear optical experiments in the low loss and diffraction free geometries with very long interaction distances [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the absence of evacuation at sufficiently long interaction lengths of the radiation with the gaseous medium, the nonlinear properties of the gas can exert a strong influence on the spectral-temporal characteristics of powerful ultrashort pulses [18,[71][72][73][74][75].…”
Section: High-power Femtosecond Pulse Propagation In Air-filled Rfmentioning
confidence: 99%
“…The propagation of femtosecond pulses in a photonic crystal fiber with a hollow core filled with atmospheric air was studied in [74]. The 2.4 MW pulse with a spectrum shifted to the long-wavelength edge of the band was obtained at the fiber output, when a 110-fs pulse with 900-nJ energy at a wavelength of 1470 nm, was launched into a three-m-long fiber.…”
Section: High-power Femtosecond Pulse Propagation In Air-filled Rfmentioning
confidence: 99%
“…However, recently, Wheeler et al demonstrated that Kagome HC-PCF could be spliced with comparable splice loss to that of PBG guiding ones, provided the HC-PCF is tapered [43] . Bandgap HC-PCF also finds applications in soliton generation [14] and pulse compression [44] . As a host for light-matter interactions [16,17] , which is one of the most advanced applications of HC-PCF, bandgap HC-PCF can enhance the interaction intensity by up to a millionfold because of its small core size and low optical attenuation.…”
Section: Comparisonmentioning
confidence: 99%